Ukrainian children’s book (1842-1916) in context of European publishing practices (by the example of French publishing practices) - Karoyeva Tetiana (Рукописна та книжкова спадщина України)

(untitled)
The goal of the research. The research aim is to investigate what Ukrainian publishers learned from the innovative publishing practice of French entrepreneurs of the 19th century. Methodology. The historical and comparative study was implemented from a methodological point of view. Scientific novelty. The development of Ukrainian children’s book publishing (1842-1916) is considered in the context of culture-based history focusing on its specific achievements and faults. Conclusions. In addition to the objective reasons for the poor development of Ukrainian children’s book publishing, the tradition of the populist understanding of the role of books in modern society had a negative meaning. The paternalistic attitude of the nationally conscious intelligentsia towards their own people, and the concentration on national education with an appeal to ethnicity limited the publishing search. Ukrainian publishers have adopted the following publishing practices: a) recognition of a children’s book asa separate type of publication with its requirements for its parameters and content; b) organization of publishing a book series; c) transition from providing educational publications toleisure publications; d) transition from moralistic publications with Christian texts to secular book publishing; e) the appearance of propaganda publications for children; f) efforts to diversify the repertoire, in particular at the expense of translated literature, luxurious editions; g) involvement of women as authors and translators; h) availability of periodicals for children. Ignoring European practice led to: a) to the absence of sustainable specialized business and marketing strategies, reliance on the public initiative of nationally conscious intelligentsia; b) neglect of children’s periodicals in marketing strategies for educating their readers, pedagogical work with parents and teachers; c) targeting cheap publications; d) weak structuring of the repertoire according to age, focusing on abstract children under 12 years old who did not differ in level of training, gender, or preferences; e) weak genre, thematic, and typological structure of the repertoire; f) neglect of parents as mediators in children’s reading.